Effect of turbulence in micro‐reactors on ultrafast competitive reactions in Cu‐Zn co‐precipitation. Issue 7 (20th February 2021) - Jiang, Xin; Chen, Shuaishuai; Chen, Xinchao; Ling, Chen; Lu, Jiangang
Abstract: The enhancement of turbulence was considered to be able to bring about better mixing and more uniform distribution of concentration generally, but its influence on ultrafast competitive reactions is an open question. Cu‐Zn co‐precipitation was carried out in three types of micro‐reactors and the turbulent intensity was regulated by changing flow rate and ultrasound power, respectively. Energy‐dispersive spectrometer of precipitates and characteristic aging time indicate the best uniformity of Cu‐Zn distribution in precipitates appears at moderate turbulent intensity. The numerical simulation shows the uniformities of precipitation both in time and in space are impacted by mixing simultaneously but with opposite direction, resulting in the appearance of maximum. The unevenness of Cu‐Zn distribution caused by inconsistent reaction rates along the time will be erased during subsequent structural evolution, while that caused by diverse reaction rates at various positions can survive and further affect the structure and performance of catalysts.